Improving wear resistance of surface layer of parts combined with electromechanical processing with tempering - V. R. Edigarov; B. Sh. Alimbaeva; S. Yu. Anokhin (Омский научный вестник)
The technology of combined electromechanical processing of machine parts with electromechanical tempering of surfaces is considered, which electromechanical processing in two passes with different values of technological factors makes it possible to obtain a modified surface layer having a multilayer structure, an upper thin softened layer, then a «white» layer, then an ordinary hardened layer and underneath is the base metal. The resulting gradient structure provides the required performance of a modified surface, primarily in terms of wear resistance determined by the running process of tribological conjugation.